Modelling of combustion characteristics of a single curved-cylinder spark-ignition crank-rocker engine - Mohammed, S.E. (MDPI AG, 2019)
A crank-rocker engine is a new invention used to convert oscillating motion from the curve-piston into the rotary motion of the crankshaft. The configuration of this new engine is different from the normal slider-crank engine, so the existing model used to calculate the combustion characteristic is not appropriate for this new engine. A fundamental thermodynamic model of a single curved-cylinder spark-ignition crank-rocker engine is presented. The model was simulated in MATLAB to predict the combustion characteristics at different operating conditions. The friction losses, residual gas fraction and combustion efficiency were introduced into the combustion model to improve the overall accuracy of the model. The developed model was used to analyze and evaluate the in-cylinder pressure, fuel burn rate, and heat release under various crank angle positions. To validate the predictions of the model, experimental tests were conducted on a single-cylinder crank-rocker engine at an engine speed of 2000 rpm, spark timing of 8.60 CA BTDC, full load and wide-open throttle (WOT) condition. Finally, the results were plotted and compared with the simulation results. The findings obtained from the current study have shown the ability of the simulation model to predict the combustion characteristics under different operating conditions. The agreement between the results of the present model and experimental data was reasonably good. This research work proposes a new model which can predict the behavior of the crank-rocker engine. The information gained from this study will aid in the tuning process and future development of this engine. Â© 2019 by the authors.